1346 - Lawrence Spriet (Medicine & Science in Sports & Exercise, 2009)
Eccrine angiomatous hamartoma is an uncommon benign cutaneous hamartoma characterized by proliferation of eccrine and vascular components. It usually presents at birth or in childhood as a solitary extremity lesion and may be associated with pain, tenderness, hypertrichosis, or hyperhidrosis. We report a 6-year-old boy with a recurrent warm, hyperhidrotic subcutaneous tumor on the lateral aspect of the right ankle. The lesion had previously been excised under the clinical impression of hemangioma and was reported as angiolipoma, but later recurred and enlarged. Clinical examination showed a flesh-colored 5 × 4.5 cm tumor with clear surface secretion. Qualitative infrared thermography demonstrated focal surface warmth over the lesion. Histopathology showed well-circumscribed unencapsulated dermal and subcutaneous nodules composed of proliferating eccrine glands, vascular channels, mucinous stroma, mature fat, dilated sweat ducts, and large vessels with organizing thrombus, confirming eccrine angiomatous hamartoma. In this case, infrared thermography converted clinically perceived warmth into a visible, non-contact surface map that may help localize symptomatic surface involvement when planning conservative excision. Histopathology remains essential for diagnosis.